Use of starch and casein edible coatings in guavas conservation (Research, Society and Development, 2020)
This study aimed to evaluate the effect of edible coatings based on starch and casein on the guavas physicochemical characteristics. The treatments were: Control (without edible coating); A (starch edible coating); AC (starch + casein edible coating); C (casein edible coating). The guavas were analyzed for weight loss, total titable acidity, total soluble solids, vitamin C and colorimetry. Starch edible coating (A) obtained lower  weight loss (10,65%). The treatments A and C conserved initial total soluble solids levels. All edible coatings were efficients in ATT conservation. Starch and casein edible coating (AC) obtained less yellowing of guavas.